Validação de jogo educativo tátil para deficientes visuais sobre drogas psicoativas - Mariano, Monaliza Ribeiro (2014)
The adaptive educational game seems a different way of acquiring information, in which the learning process is associated with ludic activities. Drug consumption is a public health issue in which those involved are vulnerable, including the person with visual impairment. Therefore, the aims of this study were: to validate Assisted Technology in the tactile game modality about psychoactive drugs for vision-impaired subjects; to develop the Knowledge Assessment (pre-test) and Game Ludic Capacity Assessment Instruments; to evaluate the Knowledge Assessment (pre-test) and Game Ludic Capacity Assessment Instruments; to measure the learning percentage of visual-impaired subjects after intervention with tactile game; to compare the percentage of information before and after using the tactile game; and to evaluate the ludic capacity of tactile game. This was a pre and post-performed quasi-experimental study, developed in the Associação de Cegos do Estado do Ceará [Ceará State Association of Blind Subjects] and in the Health Communication Laboratory, in the Nursing Department of Universidade Federal do Ceará [Ceará Federal University]. The sample included 60 subjects that were Braille-literate. Data collection happened in two stages: firstly, specialists developed and evaluated three assessment instruments. Two instruments regarded the knowledge about the subject and had questions of different difficulty levels; and another was to evaluate the game. In the second stage, the game was applied and instruments to measure learning were used. The knowledge instrument (pre-test) was applied; then, the game was used with its components (boards, game instructions, pieces, and cards); and knowledge instrument (post-test) and game evaluation were applied. Data were organized in tables and analyzed with McNemar’s test, with mean calculation. Knowledge assessment instruments were developed, each one had six questions, while the Ludic Capacity Assessment Instrument of the game included three categories, nine sub-categories, and 23 questions related to easy handling, accessibility, ludic capacity, game dynamics, among others. The mean of participants’ age was 31.5±12.5 years old and study years of 10.8±2.2. With regard to information acquisition after using the game, it was seen that the three first questions of low difficulty had a significant difference (p<0.05) with increase of right questions of pre- to post-tests (53.3, 28.3 and 16.6%). In the questions of median and high difficulties, no significant differences were found. If age range and index of right answers are associated, only the two first questions of low difficulty had a relation. The age ranges of 20 to 29 years old and 40 to 49 years old obtained relevance of right answers between pre- and post-tests (p=0.001). The right answers index/years of study association showed a significant increase (p=0.000) of right answers in the age range of 10 to 12 years of study. In the game ludic capacity assessment, the mean varied from 9.1 to 9.9. Items with the best means were: interaction of players (9.9), relevant concepts and information (9.8), indication of the game for another person (9.8), and he/she would use the game again (9.8). All items of all instrument categories had excellent means between 9.4 and 9.7, with the theoretical-methodological coherence sub-category (9.7) presenting the highest mean, and the lowest, concepts and information (9.4). This educational game was considered a valid Assisted Technology for information acquisition about drugs for visual-impaired subjects and health promotion. Health and education professionals can use such instrument as a teaching-learning strategy.